2017
DOI: 10.3399/bjgp17x693101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of primary care funding on secondary care utilisation and patient outcomes: a retrospective cross-sectional study of English general practice

Abstract: Capitation payments appear to be broadly aligned to patient need in terms of secondary care usage. Supplements to the current capitation formula are associated with reduced secondary care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…These findings complement those of a previous study which found that increased general practice capitation funding was associated with reduced emergency hospital admissions and Accident and Emergency attendances 12…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings complement those of a previous study which found that increased general practice capitation funding was associated with reduced emergency hospital admissions and Accident and Emergency attendances 12…”
Section: Discussionsupporting
confidence: 89%
“…Greater capitation spending on general practices has been found to be associated with reductions in secondary care usage and costs, and increased patient satisfaction 12. Studies have also shown that leadership within the practice organisation plays a key role in the delivery of high-quality care 13.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier 1-year cross-sectional study of English general practices found that higher capitation funding was associated with higher reported patient satisfaction in practices with GMS contracts but that there was no relationship in practices with PMS contracts. 13 The current 4-year longitudinal study has extended these findings to practices with all types of contract and has used other types of funding and a wider set of patient experience measures. Another study used pooled cross-section data and found that higher practice capitation funding is associated with higher Care Quality Commission ratings, including on the ‘responsive and caring’ domain of quality as assessed by on-site practice inspection and consideration of GPPS patient experience scores.…”
Section: Discussionmentioning
confidence: 96%
“… 7 , 11 , 12 Two cross-sectional studies have examined the association of funding and quality in English general practices. One found no consistent relationship between funding and patient satisfaction, 13 and the other found that practices with greater funding were more likely to receive higher-quality ratings from the Care Quality Commission. 14 This study expands on previous research by using a wider set of patient-reported experience measures and a longitudinal design to examine whether changes in the funding of practices are associated with changes in the experience reported by their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Primary health care is often described as the foundation of a strong health care system [ 1 ]. According to the World Health Organization (WHO) “All people, everywhere, deserve the right care, right in their community.…”
Section: Introductionmentioning
confidence: 99%